Self-assembled hypha flexible carbon electrode material and preparation method and application thereof

By using self-assembled mycelium flexible carbon electrode material, and combining porous linden wood/mycelium composite carbon powder and carbon nanotubes, the problem of cycle life decay of graphite anodes during rapid charge and discharge was solved, realizing a flexible carbon electrode with high specific surface area and structural stability, thus improving the electrochemical performance and mechanical stability of lithium-ion batteries.

CN121158768AActive Publication Date: 2025-12-19BEIHUA UNIV +1

Patent Information

Application Number
CN202511704656.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-20
Publication Date
2025-12-19
Estimated Expiration
2045-11-20

AI Technical Summary

Technical Problem

Graphite anode materials experience a significant decrease in cycle life during rapid charge and discharge, exhibiting problems such as lithium metal deposition, repeated SEI film rupture, and structural failure, leading to insufficient battery stability.

Method used

A flexible carbon electrode material with high specific surface area and structural stability is formed by combining porous linden wood/mycelium composite carbon powder, carbon nanotubes and polydopamine. This avoids traditional chemical binders, improves the connectivity of wood by treating the mycelium and adds carbon nanotubes to build conductive pathways.

Benefits of technology

It significantly improves the cycle stability and electrolyte penetration efficiency of lithium-ion batteries, enhances the specific capacitance and flexural resilience of electrodes, and provides a long-term stable application prospect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121158768A_ABST
    Figure CN121158768A_ABST
Patent Text Reader

Abstract

The invention provides a self-assembled hypha flexible carbon electrode material and a preparation method and application thereof, and belongs to the technical field of battery packs. The preparation method of the self-assembled hypha flexible carbon electrode material comprises the following steps: treating basswood with white rot fungus mycelia, crushing and roasting to obtain porous basswood / hypha composite carbon powder; and putting the porous basswood / hypha composite carbon powder and a carbon nanotube into a sterilized conical flask containing a potato glucose culture solution, inoculating gloeophyllum trabeum, performing activation culture, adding a dopamine hydrochloride aqueous solution, performing polymerization after ultraviolet irradiation, taking out and tabletting to obtain the self-assembled hypha flexible carbon electrode material. In the preparation process of the self-assembled hypha flexible carbon electrode material, the flexible carbon electrode material is synthesized by taking porous basswood / hypha composite carbon powder as a matrix, taking gloeophyllum trabeum hypha as an adhesive, taking polydopamine as a reinforcing agent and adding carbon nanotubes as a conductive reinforcing material, so that the technical problem of poor cycle performance of a lithium ion battery is solved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of battery packs, and particularly relates to a self-assembled mycelium flexible carbon electrode material and a preparation method and application thereof. BACKGROUND

[0002] Secondary lithium ion batteries have the advantages of high working voltage, high energy density, light weight, long cycle life and environmental friendliness, and are therefore widely used in power batteries, 3C batteries and energy storage fields.

[0003] At present, graphite materials, as the most mainstream commercialized negative electrode materials, have the characteristics of low cost, good electronic conductivity, low lithium ion insertion / extraction potential (close to the lithium metal potential) and relatively optimal cycle stability. They exhibit good rate performance and long cycle life under stable working conditions. However, with the increasing demand for fast charging capability in applications such as electric vehicles and portable electronic devices, the problem of significant cycle life decay of graphite negative electrodes in high-speed charging and discharging processes has become increasingly prominent.

[0004] The main reasons for the performance decay of graphite negative electrodes under fast charging and long cycle conditions include the following aspects: firstly, lithium metal deposition on the surface is easy to occur in the process of fast lithium ion insertion, which not only leads to irreversible loss of active lithium, but also may cause safety hazards such as internal short circuit of the battery; secondly, the volume change of the graphite layered structure occurs in the repeated charging and discharging process, which may cause the generation of microcracks and structural damage in the long term; in addition, the solid electrolyte interface (SEI film) on the surface of graphite is easy to repeatedly break and reconstruct under large current or low temperature conditions, continuously consuming electrolyte and increasing interface impedance, causing capacity decay and life decline; on the other hand, electrolyte solvent molecules may co-insert into the graphite interlayer with lithium ions, causing layer peeling and further accelerating structural failure.

[0005] Therefore, although graphite as a traditional negative electrode material performs well in conventional applications, its stability under fast charging and long cycle conditions still has obvious deficiencies, and further exploration of efficient and industrialized strategies is still needed. SUMMARY

[0006] Therefore, the application provides a self-assembled mycelium flexible carbon electrode material and a preparation method and application thereof to solve the technical problem of poor cycle performance of lithium ion batteries.

[0007] To achieve the above application purposes, the application provides a self-assembled mycelium flexible carbon electrode material, raw materials of which include porous basswood / mushroom composite carbon powder, schizophyllum commune, carbon nanotubes, dopamine hydrochloride and potato glucose culture solution.

[0008] A preparation method of the self-assembled mycelium flexible carbon electrode material in the application includes the following steps: S1, put the linden wood and the white rot fungus mycelium together into the disposable solid culture medium according to the mass ratio of 80-100:1, and then put into the constant temperature and humidity incubator for culture at 28-30℃, to obtain the linden wood / mycelium composite substrate; S2, crush the linden wood / mycelium composite substrate, heat to 800-900℃ under the atmosphere of nitrogen, keep warm for 1.5-2h, and then cool to room temperature, to obtain the porous linden wood / mycelium composite carbon powder; S3, put the porous linden wood / mycelium composite carbon powder and the carbon nanotube into the conical flask containing the sterilized potato dextrose culture solution, inoculate the gregariochete, and the mass ratio of the porous linden wood / mycelium composite carbon powder to the gregariochete is 20-30:1; S4, place the conical flask in the shaking bed for activation culture, wash with deionized water, add the dopamine hydrochloride aqueous solution, then irradiate with ultraviolet light, continue to place in the shaking bed, and then take out after polymerization to press into tablets, to obtain the self-assembled mycelium flexible carbon electrode material.

[0009] Preferably, the heating rate in S2 is 3-5℃ / min.

[0010] Preferably, the mass ratio of the porous linden wood / mycelium composite carbon powder to the carbon nanotube in S3 is 0.25-1:1.

[0011] Preferably, the mass concentration of the dopamine hydrochloride aqueous solution in S4 is 0.2-0.4 g / L.

[0012] Preferably, the mass ratio of the dopamine hydrochloride aqueous solution to the porous linden wood / mycelium composite carbon powder in S4 is 0.4-0.6:1.

[0013] Preferably, the specific surface area of the porous linden wood / mycelium composite carbon powder in S2 is 400.82 m 2 / g-487.33 m 2 / g.

[0014] The self-assembled mycelium flexible carbon electrode material in the application is applied to the lithium ion battery negative material and the battery pack.

[0015] Preferably, the self-assembled mycelium flexible carbon electrode material is applied to the lithium ion battery negative material including the following steps: mix the self-assembled mycelium flexible carbon electrode material with the conductive agent carbon black and the binder PVDF, make the slurry, coat on the copper current collector, dry, and then stamp through the stamping machine to obtain the lithium ion battery negative material.

[0016] Further preferably, the mass ratio of the self-assembled mycelium flexible carbon electrode material to the conductive agent carbon black and the binder PVDF is 6-10:2:1.

[0017] In the preparation of the self-assembled mycelial flexible carbon electrode material of this invention, porous linden wood / mycelial composite carbon powder is used as the matrix, *Cladosporium glomeratum* mycelium as the binder, and polydopamine as the reinforcing agent. Carbon nanotubes are further added as a conductive reinforcing material, synthesizing a polydopamine / carbon nanotube modified mycelial / carbon flexible electrode material. This avoids the use of traditional chemical binders and achieves uniform composite and green preparation of the material at the molecular scale. First, linden wood is treated with white-rot fungus mycelium. The mycelium can grow on its own and become a novel composite material with the wood. Simultaneously, the fungal treatment improves the wood's connectivity, increases specific surface area, and improves surface wettability. The dopamine-synergistic mycelial-assembled flexible carbon electrode material has a porous structure with a large specific surface area and structural stability. The introduction of polydopamine significantly improves the surface wettability of the material, enhances electrolyte penetration and ion transport efficiency, and greatly enhances the electrode's specific capacitance and cycle stability. Further addition of carbon nanotubes to construct efficient conductive pathways in the mycelial network, synergistically enhances interfacial bonding and structural stability with polydopamine, and exhibits excellent flexural resilience and environmental stability, making it a promising candidate for long-term stable applications. Attached Figure Description

[0018] Figure 1 HDT / CNT in a specific embodiment of the present invention 0.5 HDT / CNT 0.25 @PDA、HDT / CNT 0.5 SEM images of @PDA and HDT / CNT1@PDA (where ab is HDT / CNT1). 0.5 SEM image, cd is HDT / CNT 0.25 SEM image of @PDA, ef is HDT / CNT 0.5 SEM image of @PDA, gh is SEM image of HDT / CNT1@PDA). Figure 2 HDT / CNT in a specific embodiment of the present invention 0.5 HDT / CNT 0.25 @PDA、HDT / CNT 0.5 Nitrogen adsorption-desorption curves (ad) and corresponding pore size distribution diagrams (eh) for @PDA and HDT / CNT1@PDA; Figure 3 HDT / CNT in a specific embodiment of the present invention 0.5 The contact angle test results are shown in the figure. Figure 4 HDT / CNT in a specific embodiment of the present invention 0.5 @PDA contact angle test results diagram; Figure 5 For 10 mV·s -1HDT / CNT at different scan rates 0.5 HDT / CNT 0.25 @PDA, HDT / CNT 0.5 CV curve of @PDA and HDT / CNT Figure 6 HDT / CNT 0.5 HDT / CNT 0.25 @PDA, HDT / CNT 0. 5 GCD curve of @PDA, HDT / CNT at 0.2 mA / cm 2 current density; Figure 7 HDT / CNT 0.5 HDT / CNT 0.25 @PDA, HDT / CNT 0. 5 Impedance plot of @PDA, HDT / CNT Figure 8 HDT / CNT 0.5 CV curve of @PDA at different scan rates (10, 20, 50, 100, 200 mV / s); Figure 9 HDT / CNT 0.5 Galvanostatic charge-discharge curve of @PDA; Figure 10 HDT / CNT 0.5 HDT / CNT 0.25 @PDA, HDT / CNT 0. 5 Area specific capacitance plot of @PDA based on galvanostatic charge-discharge curve; Figure 11 HDT / CNT 0.5 Cycling stability plot of @PDA at 0−0.8 V potential window and 5 mA / cm 2 current density; Figure 12 HDT / CNT 0.5 Capacitance performance test plot of @PDA before and after bending 100 times; Figure 13 HDT / CNT 0.5 Real object plot of @PDA after drying for 30 days; Figure 14 HDT / CNT 0.5 Real object plot of @PDA after simple water immersion treatment; Figure 15 Bending state plot of real object in Figure 14 ; Figure 16 HDT / CNT 0.25 @Battery capacity performance chart of PDA flexible carbon material as lithium ion battery negative electrode Figure 17 HDT / CNT 0.25 @Cycle performance chart of PDA flexible carbon material as lithium ion battery negative electrode at a current density of 1.0 A / g. DETAILED DESCRIPTION

[0019] In order to make the objects, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions of the embodiments of the present application will be described clearly and completely below with reference to the drawings of the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. Based on the described embodiments of the present application, all other embodiments obtained by a person of ordinary skill in the art without any inventive effort fall within the scope of protection of the present application.

[0020] Embodiment 1 The present embodiment provides a preparation method of a self-assembled mycelium flexible carbon electrode material, comprising the following steps: S1, put the linden wood and the white rot fungus mycelium into the disposable solid culture medium according to a mass ratio of 100:1, and then put them into a constant temperature and humidity incubator (60% RH) for 28°C culture for 7 days, so as to obtain a linden wood / mycelium composite substrate after the white rot fungus removes part of the lignin in the linden wood; In this step, part of the lignin in the linden wood is removed because the wood cell wall is a dense structure formed by the interaction between cellulose, hemicellulose and lignin. Lignin, as an important component of plant cell wall, fills in the cell wall in the form of crust material, forming a firm natural physical barrier in the cell wall. The connectivity between wood cells is mainly determined by the size and number of micropores on the effective pit membrane, and the complexity and unevenness of the cell wall reduce the connectivity of the wood, hindering the migration of ions in the pore channel. Therefore, removing lignin and increasing the effective pore channel on the wood cell wall is an important means to ensure ion transmission. During the fungus treatment, the mycelium has become a new composite material with the wood through its own growth, and the fungus treatment can improve the connectivity of the wood, increase the specific surface area and improve the surface wettability. If all the lignin is removed, the proportion of micropores in the wood will decrease, and the proportion of macropores will increase. Macropores are not conducive to the storage of electric charges due to their large internal free space, and mesopores and micropores are more conducive to the rapid transmission of electrolyte and the rapid storage of electric charges, thereby improving the energy storage and rate performance of micropores.

[0021] S2, crush the linden wood / mycelium composite substrate and heat it to 800°C under a nitrogen atmosphere at a heating rate of 3°C / min, keep it for 2h, and then reduce it to room temperature to obtain a porous linden wood / mycelium composite carbon powder; S3, the porous linden wood / mycelium composite carbon powder and carbon nanotubes are mixed according to a mass ratio of 0.25:1, then placed in a conical flask containing sterilized potato dextrose culture solution (the mass of the culture solution is 1000 times that of the porous linden wood / mycelium composite carbon powder), and inoculated with gloeophyllum trabeum, the mass ratio of the porous linden wood / mycelium composite carbon powder to the gloeophyllum trabeum being 20:1; Gloeophyllum trabeum is a brown rot fungus that can mainly decompose cellulose and hemicellulose in wood. The fruiting body of gloeophyllum trabeum presents a labyrinth, pleated or dentiform shape, and thus has certain expansion and contraction performance, which is suitable for preparing flexible materials. Meanwhile, the optimal growth temperature range of gloeophyllum trabeum is wide, which can slowly grow at a low temperature (such as 10°C) and can also tolerate a high temperature (up to 40°C), which is beneficial to industrialized production.

[0022] The mycelium of gloeophyllum trabeum can form a certain network structure during growth, which can penetrate between the porous linden wood / mycelium composite carbon powder and the carbon nanotubes, and enhance the overall structural strength and stability of the material. Meanwhile, the presence of the mycelium can also help to form a more abundant pore structure and increase the specific surface area of the material, which is very beneficial to improving the electrochemical performance of the electrode material, such as providing more active sites for electrode reactions and promoting the penetration and ion transmission of electrolyte.

[0023] Participate in biological transformation and modification: gloeophyllum trabeum can perform a series of metabolic activities during cultivation, and the metabolic products can affect the surface properties of the composite carbon powder and the carbon nanotubes and perform biological modification. This modification can improve the chemical activity of the material surface, making it more conducive to reaction with subsequently added dopamine hydrochloride, thereby promoting the self-assembly process and improving the performance of the electrode material.

[0024] Preparation process of potato dextrose (PDB) culture solution: 200 g of peeled potatoes are boiled with water to obtain 1 L of potato liquid, 20 g of glucose, 3 g of KH2PO4, 1.5 g of MgSO4·7H2O, and 0.008 g of thiamine are added, and the pH is 6.0±0.2 (25°C); S4, the conical flask is placed in a shaker, the temperature can be 28°C, the shaking speed is 150 rpm, and the activation culture is performed for 5 days. After washing with deionized water, 0.2 g / L of dopamine hydrochloride aqueous solution is added, the mass ratio of the dopamine hydrochloride aqueous solution to the porous linden wood / mycelium composite carbon powder being 0.4:1, then the mixture is irradiated with ultraviolet light for 30 minutes, and then the mixture is placed in a shaker, the temperature of the shaker is 28°C, and the shaking speed is 150 rpm. After 2 days of polymerization, the mixture is taken out and pressed into a tablet to obtain a self-assembled mycelium flexible carbon electrode material (HDT / CNT 0.25 @PDA).

[0025] The dispersibility and interface binding force of CNTs on the mycelium surface can be effectively improved by PDA modification, and the conductivity and mechanical properties of the composite material are also enhanced.

[0026] The application of the self-assembled mycelium flexible carbon electrode material in the negative electrode material of a lithium ion battery and a battery pack. The self-assembled mycelium flexible carbon electrode material in the negative electrode material of a lithium ion battery comprises the following steps: mixing the self-assembled mycelium flexible carbon electrode material, conductive agent carbon black and binder PVDF in a mass ratio of 6:2:1, preparing a slurry and coating the slurry on a copper current collector, and performing vacuum drying treatment at 60 DEG C for 12 hours, and then stamping the dried material by a stamping machine to obtain the negative electrode material of a lithium ion battery.

[0027] Embodiment 2 The embodiment provides a preparation method of a self-assembled mycelium flexible carbon electrode material, comprising the following steps: S1, put the linden wood and the white rot fungus mycelium into a disposable solid culture medium in a mass ratio of 90:1, and then put them into a constant temperature and humidity incubator for culture at 29 DEG C for 7 days to obtain a linden wood / mycelium composite substrate; S2, crush the linden wood / mycelium composite substrate, heat it to 850 DEG C under a nitrogen atmosphere at a heating rate of 4 DEG C / min, and keep the temperature for 1.7 h, and then reduce the temperature to room temperature to obtain a porous linden wood / mycelium composite carbon powder; S3, mix the porous linden wood / mycelium composite carbon powder and carbon nanotubes in a mass ratio of 0.5:1, and then put them into a conical flask containing sterilized potato dextrose culture solution (the mass of the culture solution is 1000 times that of the porous linden wood / mycelium composite carbon powder), inoculate the Diderma bicolor, and the mass ratio of the porous linden wood / mycelium composite carbon powder to the Diderma bicolor is 25:1; The composition of the potato dextrose (PDB) culture solution is as follows: 200 g of peeled potato is boiled with water to obtain 1 L of potato liquid, 20 g of glucose, 3 g of KH2PO4, 1.5 g of MgSO4·7H2O and 0.008 g of thiamine are added, and the pH is 6.0±0.2 (25 DEG C); S4, place the conical flask in a shaking bed, the temperature can be 28 DEG C, the shaking speed is 150 rpm, activate the culture for 5 days, wash with deionized water, add a 0.4 g / L hydrochloric acid dopamine aqueous solution, the mass ratio of the hydrochloric acid dopamine aqueous solution to the porous linden wood / mycelium composite carbon powder is 0.5:1, then irradiate under ultraviolet light for 30 minutes, continue to place the conical flask in the shaking bed, the temperature of the shaking bed is 28 DEG C, the shaking speed is 150 rpm, and after 2 days of polymerization, take out the conical flask, stamp it to obtain the self-assembled mycelium flexible carbon electrode material (HDT / CNT 0.5 @PDA).

[0028] The application of the self-assembled mycelium flexible carbon electrode material in the negative electrode material of a lithium ion battery and a battery pack. The self-assembled mycelium flexible carbon electrode material in the negative electrode material of a lithium ion battery comprises the following steps: mixing the self-assembled mycelium flexible carbon electrode material, conductive agent carbon black and binder PVDF according to a mass ratio of 7:2:1, preparing slurry and coating on a copper current collector, and performing vacuum drying treatment at 60 DEG C for 12 hours, and then stamping through a stamping machine to obtain the negative electrode material of a lithium ion battery.

[0029] Embodiment 3 The embodiment provides a preparation method of a self-assembled mycelium flexible carbon electrode material, comprising the following steps: S1, putting linden wood and white rot fungus mycelium together into disposable solid culture medium according to a mass ratio of 80:1, and then putting into a constant temperature and humidity incubator for culture at 30 DEG C to obtain linden wood / mycelium composite substrate; S2, crushing the linden wood / mycelium composite substrate, heating to 900 DEG C under a nitrogen atmosphere at a heating rate of 5 DEG C / min, and keeping for 1.5 h, and then reducing to room temperature to obtain porous linden wood / mycelium composite carbon powder; S3, mixing the porous linden wood / mycelium composite carbon powder and carbon nanotubes according to a mass ratio of 1:1, and then putting into a conical flask containing sterilized potato dextrose culture solution (the mass of the culture solution is 1000 times that of the porous linden wood / mycelium composite carbon powder), and inoculating gregarius gregarine, and the mass ratio of the porous linden wood / mycelium composite carbon powder to the gregarius gregarine is 30:1; The composition of the potato dextrose (PDB) culture solution is as follows: peeling potatoes 200 are boiled into 1 L of potato liquid, 20 g of glucose, 3 g of KH2PO4, 1.5 g of MgSO4·7H2O, 0.008 g of thiamine, pH: 6.0±0.2 (25 DEG C); S4, putting the conical flask into a shaking bed, the temperature can be 28 DEG C, the shaking speed is 150 rpm, and the activation culture is performed for 5 days, then washing with deionized water, adding 0.3 g / L of hydrochloric acid dopamine aqueous solution, the mass ratio of the hydrochloric acid dopamine aqueous solution to the porous linden wood / mycelium composite carbon powder is 0.6:1, then irradiating under ultraviolet light for 30 minutes, and then putting into the shaking bed again, the temperature of the shaking bed is 28 DEG C, the shaking speed is 150 rpm, and the tablet is taken out after 2 days of polymerization to obtain the self-assembled mycelium flexible carbon electrode material (HDT / CNT1@PDA).

[0030] The application of the self-assembled mycelium flexible carbon electrode material in the lithium ion battery negative material and the battery pack. The self-assembled mycelium flexible carbon electrode material in the lithium ion battery negative material comprises the following steps: the self-assembled mycelium flexible carbon electrode material, the conductive agent carbon black and the binder PVDF are mixed in a mass ratio of 10:2:1, a slurry is prepared and coated on a copper current collector, and vacuum drying treatment is carried out at 60 DEG C for 12 hours, and then the lithium ion battery negative material is obtained through a punching machine.

[0031] Comparative Example 1 The present comparative example is similar to Example 1, except that in the present comparative example, the mass ratio of basswood to white rot fungus mycelium is 50:1, and the mass ratio of porous basswood / mycelium composite carbon powder to Tremella fuciformis is 10:1.

[0032] Comparative Example 2 The present comparative example is similar to Example 1, except that in the present comparative example, the mass ratio of basswood to white rot fungus mycelium is 120:1, and the mass ratio of porous basswood / mycelium composite carbon powder to Tremella fuciformis is 60:1.

[0033] Comparative Example 3 The present comparative example is similar to Example 2, except that in the present comparative example, the dopamine hydrochloride solution in S4 is replaced by water, and the obtained electrode material is HDT / CNT 0.5 .

[0034] Performance test The electrochemical performance of the prepared battery pack can be predicted from the perspective of the microstructure of the electrode material, the capacitance performance before and after bending, the cyclic voltammetry curve, the constant current charge-discharge curve, the cycle stability and the specific capacitance. Based on this, the electrode material or intermediate product is tested as follows.

[0035] (1) The porous basswood / mycelium composite carbon powder in Examples 1-3 and Comparative Examples 1-2 is measured for the lignin content and the specific surface area (m 2 / g). The test results are shown in Table 1. The measurement steps of the lignin content are as follows: 1 g of the porous basswood / mycelium composite carbon powder is accurately weighed, wrapped with filter paper and subjected to degreasing treatment; 15 mL of 72% sulfuric acid is added to a 100 mL beaker, and the mixture is kept in a 15 DEG C cold water bath for 4 hours; the mixture obtained in step 2 is diluted to a 3% sulfuric acid concentration (i.e. the total mixture is 560 ml), and refluxed for 3 hours; the residue is filtered and washed, dried to constant weight, weighed and the lignin content is calculated.

[0036] Table 1 Lignin content and pore analysis of the porous basswood / mycelium composite carbon powder of each group The self-assembled mycelium flexible carbon electrode material in Examples 1-3 and Comparative Examples 1-2 was taken to measure the bendable angle of the electrode material and the capacitance retention rate of the electrode material after bending, as shown in Table 2.

[0037] Table 2 Bendable angle of electrode material and capacitance retention rate of electrode material after bending White rot fungi is a fungus that selectively removes lignin. In the process of removing lignin, it does not affect cellulose and hemicellulose, so other fungi cannot be used instead. In the process of fungal treatment, mycelium can grow into a new composite material with wood, and fungal treatment can improve wood connectivity, increase specific surface area, and improve surface wettability.

[0038] Reasonable partial removal of lignin causes the cell wall itself to swell and delaminate due to the loss of support, exposing a large number of nanoscale pores. Wood is completely transformed from a dense structure with only limited channels into a highly interconnected three-dimensional porous network from nanometers to microns. Therefore, when lignin is partially removed, the specific surface area of wood increases significantly, and when it is used as an electrode material, it provides more active sites for charge storage and transfer, which means that it can carry higher energy density for batteries.

[0039] However, excessive removal of lignin will reduce the proportion of micropores in wood and increase the proportion of macropores, which will reduce the specific surface area; at the same time, the reduction in the number of micropores increases the straight-line distance from the electrolyte phase to the energy storage site, reducing the specific capacitance.

[0040] The mycelium of the Meripilus giganteus forms a certain network structure during growth, which can penetrate between the porous linden wood / mycelium composite carbon powder and carbon nanotubes, enhancing the overall structural strength and stability of the material. When the Meripilus giganteus quality is relatively high, the adhesion is better and the material is more flexible, so the bendable angle is larger. When the Meripilus giganteus quality is relatively low, the adhesion is poor and the material is more brittle, so the bendable angle is smaller. When the Meripilus giganteus quality is relatively high, the proportion of biomass carbon decreases, and the capacitance retention rate decreases after multiple bending. When the Meripilus giganteus quality is relatively low, the proportion of biomass carbon increases, and the capacitance retention rate improves after multiple bending.

[0041] Limiting the mass ratio of white-rot fungus mycelium to basswood: the core is to adjust the degree of lignin removal in basswood by controlling the amount of white-rot fungus. Too little will result in too much lignin residue, blocking the pores of basswood, making the specific surface area of the composite carbon powder obtained by subsequent carbonization small, and the active sites insufficient, affecting the initial capacitance performance; too much will excessively degrade lignin, destroy the fiber skeleton of basswood, and cause the mechanical strength of the carbon powder to drop sharply, making the subsequent electrode material prone to brittle fracture. Only within this ratio range can lignin be removed moderately, both retaining the porous structure of the carbon powder to ensure the capacitance basis and maintaining sufficient skeleton strength to support subsequent processing.

[0042] At the same time, limit the mass ratio of Meripilus giganteus to porous basswood / mycelium composite carbon powder: the core is to optimize the flexibility and structural stability of the electrode material on the basis of the former. Meripilus giganteus needs to grow moderately in the pores of the carbon powder, and the mycelial network formed can connect the carbon powder particles like a bond, and synergistically improve the flexibility of the material; too much will block the pores of the carbon powder, reducing the active sites, and too little will not form a complete mycelial network, and will not play a role in enhancing flexibility. However, the effect of this ratio depends on the former - if the former is imbalanced, resulting in a too brittle or insufficiently porous carbon powder structure, Meripilus giganteus either cannot grow normally or will further damage the carbon powder skeleton, losing the significance of optimizing flexibility.

[0043] The amount of white-rot fungus mycelium and Meripilus giganteus used together determines the bendable angle of the electrode material and the capacitance retention rate after bending. The former controls the amount of lignin removal to create a high-quality substrate with "porous + strong skeleton" for the carbon powder, which is a prerequisite for the electrode to have initial capacitance and bending resistance; the latter strengthens the flexible connection between carbon powders through the mycelial network, so that the material does not damage the porous structure and conductive network when bending, avoiding the loss of capacitance. Only when both are within the appropriate range can the capacitance performance, mechanical strength, and flexibility of the electrode be balanced, and the goal of high capacitance retention rate after bending can be achieved.

[0044] (2) HDT / CNT 0.5 , HDT / CNT 0.25 @PDA, HDT / CNT 0.5 @PDA and HDT / CNT1SEM images of Figure 1 HDT / CNT 0.5 @PDA, c-d are SEM images of HDT / CNT 0.25 @PDA, e-f are SEM images of HDT / CNT 0.5SEM images of @PDA and gh are SEM images of HDT / CNT1@PDA. A uniform thin film can be seen forming on the surface, proving that the PDA was successfully loaded. The carbon nanotubes may be encapsulated by the PDA, resulting in better dispersion of CNTs and reduced aggregation. The presence of carbon nanotubes provides many binding sites for the loading of PDA nanoparticles, which helps to improve the fast charging and mass transfer process on the electrode surface.

[0045] (3) HDT / CNT 0.5 HDT / CNT 0.25 @PDA、HDT / CNT 0.5 Nitrogen adsorption-desorption curves (ad) and corresponding pore size distribution diagrams (eh) for @PDA and HDT / CNT1@PDA are shown below. Figure 2 .

[0046] Depend on Figure 2 It can be seen that HDT / CNT 0.5 HDT / CNT 0.25 @PDA, HDT / CNT 0. 5 The pore volume, average pore diameter, and specific surface area of ​​@PDA, HDT / CNT1@PDA are shown in Table 3.

[0047] Table 3. Pore volume, average pore diameter, and specific surface area of ​​electrode materials. (4) Take HDT / CNT 0.5 The contact angle test results are as follows Figure 3 HDT / CNT 0.5 @PDA contact angle test results are as follows Figure 4 It can be seen that HDT / CNT 0.5 and HDT / CNT 0.5 The water contact angle of the @PDA is less than 90°, proving that the material surface is hydrophilic. (Sample HDT / CNT) 0.5 The initial contact angle is 70°, indicating that HDT / CNT 0.5 The surface exhibits some hydrophilicity, but it is relatively weak. This hydrophilicity may originate from certain hydrophilic groups (such as hydroxyl and carboxyl groups) on the surface of the hyphae and carbon nanotubes (CNTs). The contact angle drops to 0° after 0.5 seconds, indicating that the sample surface has the ability to rapidly absorb water or spread liquid. This phenomenon may be due to the rapid interaction between the hydrophilic groups of the hyphae and water molecules upon contact. HDT / CNT 0.5 The initial contact angle of the PDA is 20°, indicating HDT / CNT. 0.5The PDA surface exhibits extremely high hydrophilicity, primarily derived from the polydopamine (PDA) coating. PDA is rich in hydrophilic groups such as hydroxyl and amino groups. The contact angle drops to 0° after 0.5 seconds, indicating that the PDA coating further enhances the surface's superhydrophilicity. The strong interaction between the hydrophilic groups of PDA and water molecules leads to rapid liquid spread. The PDA coating improves the hydrophilicity of CNTs, reduces the contact angle, and enhances wettability. The combination of PDA and CNTs not only improves wettability but also maintains the mechanical and electrical properties of CNTs, achieving multifunctionality.

[0048] (5) HDT / CNT 0.5 HDT / CNT 0.25 @PDA, HDT / CNT 0. 5 @PDA, HDT / CNT1@PDA was used as the working electrode (1 cm × 1 cm), and Pt sheet and Ag / AgCl electrode were used as the counter electrode and reference electrode, respectively. In a three-electrode system with 1 M Na2SO4 electrolyte and a voltage window of 0–0.8 V, the electrochemical characteristics of the electrode materials were measured. The measurement results are as follows: Figures 5 to 11 .

[0049] like Figure 5 For 10 mV·s -1 At the scanning rate, the CV curves are basically rectangular. Figure 6 HDT / CNT was displayed. 0.5 HDT / CNT 0.25 @PDA、HDT / CNT 0. 5 @PDA, HDT / CNT1@PDA at 0.2 mA / cm 2 The GCD curves at current density are shown in the figure. It can be seen that the GCD curves of all samples exhibit a near-isosceles triangle shape. Furthermore, at the same current density, HDT / CNT... 0. 5 @PDA and HDT / CNT1 @PDA electrode materials have longer charge / discharge times than the other two electrode materials. 0. 5 @PDA exhibits better ion storage performance. Figure 7 For AC impedance diagrams of different electrode materials, HDT / CNT in the low-frequency region 0.5 The higher slope of the @PDA indicates better capacitance performance. In the high-frequency region, the semicircle represents the charge transfer resistance, HDT / CNT. 0. 5 The smallest semicircle of @PDA indicates a smaller charge transfer resistance.

[0050] from Figure 7 As can be seen from this, HDT / CNT 0.5The half-diameter (representing charge transfer impedance) in the high-frequency region is likely the largest among all samples. This indicates that lithium ions encounter very high resistance when crossing the electrode / electrolyte interface. High impedance leads to poor battery rate performance (difficulty charging and discharging at high currents), severe polarization (significant voltage hysteresis), and low power density. HDT / CNT 0.25 @PDA and HDT / CNT 0.5 @PDA exhibits the smallest impedance arc. This indicates that the PDA coating provides a uniform and highly lithium-ion-conducting interface layer, significantly reducing charge transfer impedance and thus improving the battery's rate performance and reaction kinetics.

[0051] Further analysis of the HDT / CNT samples 0. 5 @PDA is being tested. Figure 8 HDT / CNT was showcased 0.5 The cyclic voltammetry curves of the @PDA at different scan rates (10, 20, 50, 100, 200 mV / s) all show an approximate rectangle, indicating that the electrode is mainly composed of double-layer capacitance. Figure 9 Display HDT / CNT 0.5 The constant current charge-discharge curve of the PDA is a symmetrical triangle, indicating that it has good reversibility. Figure 10 The areal capacitance is calculated based on the constant current charge-discharge curve. (HDT / CNT) 0. 5 At current densities of 0.2, 0.5, 1, and 2 mA / cm² 2 The areal capacitances at these locations are 26.81, 19.96, 15.38, and 10.13 mF / cm². 2 HDT / CNT 0.25 @PDA at current densities of 0.2, 0.5, 1, and 2 mA / cm 2 The areal capacitances at these locations are 22.63, 11.69, 6.90, and 3.51 mF / cm². 2 HDT / CNT 0.5 @PDA at current densities of 0.2, 0.5, 1, and 2 mA / cm 2 The area capacitances at these locations are 346.54, 269.81, 180.53, and 105.23 mF / cm². 2 HDT / CNT1@PDA at current densities of 0.2, 0.5, 1, and 2 mA / cm² 2 The areal capacitances at these locations are 380.96, 392.77, 304.88, and 239.80 mF / cm². 2 HDT / CNT 0.5 The area capacitance of the PDA electrode material is significantly optimal, indicating that the conductivity is enhanced by the synergistic effect of appropriate CNTs and PDA modification, thus improving the specific capacitance of the electrode material.

[0052] Figure 11 For HDT / CNT 0.5 @PDA in a potential window of 0−0.8V and 5 mA / cm 2 Cyclic stability at current density. After 10,000 cycles, its capacitance retention was 97.10%. Furthermore, after 10,000 cycles, the constant current charge-discharge spectrum maintained a relatively symmetrical slope consistent with the initial values. Capacitance characteristics under normal and bending conditions at a scan rate of 10 mV / s were evaluated using CV measurements. After 100 bending cycles, from... Figure 12 As can be seen, the material remains intact, and the bending state has little impact on the capacitance performance of the HDT / CNTs@PDA composite material; the CV curve shows almost no distortion. This indicates that the prepared electrode material has good flexibility. Furthermore, the composite material possesses a certain degree of self-healing ability. HDT / CNTs 0.5 @PDA will naturally shrink and become brittle after 30 days of drying. Figure 13 However, after simple water immersion treatment, its size increased and it was able to recover some of its original size. Figure 14 At the same time, it still has good elasticity, as shown in the bending diagram. Figure 15 This flexibility can be attributed to the natural mechanical support and porous structure provided by the mycelium and wood-based carbon powder, the enhanced conductivity and mechanical strength by CNTs, and the optimized interfacial bonding and elasticity by PDA. This multi-component synergistic effect endows the composite material with high elasticity, high mechanical strength, and excellent electrochemical performance. Furthermore, the combination of good electrochemical performance and flexibility means that this material can be widely used in wearable devices, flexible sensors, and other high-tech fields, paving the way for more efficient and convenient intelligent systems.

[0053] Figure 16 For HDT / CNT 0.25 The battery capacity performance graph shows that the PDA flexible carbon material (the electrode material in Example 1) is used as the negative electrode in a lithium-ion battery. It can be seen that the average specific discharge capacities of this electrode at current densities of 0.1, 0.2, 0.5, 1.0, 2.0, and 5.0 A / g are 521.8, 409.8, 362.2, 285.4, 187.3, and 122.3 mAh / g, respectively. Even when the current density increases from 0.1 A / g to 5.0 A / g, it still exhibits a rate performance of 23.5%. When the current density recovers to 0.1 A / g, the reversible capacity is 493.5 mAh / g, with a capacity recovery rate of 92.3%. For practical applications, providing excellent rate performance and recovery capacity is crucial.

[0054] Figure 17The cycle performance of HDT / CNT0.25@PDA flexible carbon material (the electrode material in Example 1) as a lithium ion battery anode at a current density of 1.0 A / g is shown in the figure. After 200 cycles, the electrode still maintains a high specific capacity of 272.8 mAh / g (the capacity retention rate is 95% compared with the second cycle), and the coulombic efficiency is as high as 99.66%. The excellent capacity retention rate and nearly 100% coulombic efficiency reflect the HDT / CNT 0.25 @PDA flexible carbon material as a lithium ion battery anode material.

[0055] The specific embodiments of the application described above do not constitute a limitation of the protection scope of the application. Any various other corresponding changes and modifications made according to the technical concept of the application should be included in the protection scope of the claims of the application.

Claims

1. A self-assembled mycelial flexible carbon electrode material, characterized in that, Its raw materials include porous linden wood / mycelium composite carbon powder, *Gyromitra spp.*, carbon nanotubes, dopamine hydrochloride, and potato dextrose culture medium.

2. A method for preparing a self-assembled mycelial flexible carbon electrode material as described in claim 1, characterized in that, Includes the following steps: S1. Linden wood and white rot fungus mycelium are placed together in a disposable solid culture medium at a mass ratio of 80-100:1, and then placed in a constant temperature and humidity incubator at 28-30℃ to obtain linden wood / mycelium composite substrate. S2. After crushing the linden wood / mycelium composite substrate, heat it to 800-900℃ in a nitrogen atmosphere, keep it at that temperature for 1.5-2 hours, and then cool it to room temperature to obtain porous linden wood / mycelium composite carbon powder. S3. Place the porous linden wood / mycelium composite carbon powder and carbon nanotubes into a sterilized conical flask containing potato glucose culture medium, and inoculate with *Cladosporium glomeratum*. The mass ratio of the porous linden wood / mycelium composite carbon powder to *Cladosporium glomeratum* is 20-30:

1. S4. The conical flask is placed in a shaker for activation and culture, washed with deionized water, and then dopamine hydrochloride aqueous solution is added. After ultraviolet light irradiation, it is placed back in the shaker. After polymerization, it is taken out and pressed into tablets to obtain self-assembled mycelial flexible carbon electrode material.

3. The method for preparing the self-assembled mycelial flexible carbon electrode material according to claim 2, characterized in that, The heating rate described in S2 is 3-5℃ / min.

4. The method for preparing the self-assembled mycelial flexible carbon electrode material according to claim 2, characterized in that, The mass ratio of porous linden / mycelium composite carbon powder to carbon nanotubes in S3 is 0.25-1:

1.

5. The method for preparing the self-assembled mycelial flexible carbon electrode material according to claim 2, characterized in that, The mass concentration of the dopamine hydrochloride aqueous solution in S4 is 0.2-0.4 g / L.

6. The method for preparing the self-assembled mycelial flexible carbon electrode material according to claim 2, characterized in that, The mass ratio of the dopamine hydrochloride aqueous solution to the porous linden / mycelium composite carbon powder in S4 is 0.4-0.6:

1.

7. The method for preparing the self-assembled mycelial flexible carbon electrode material according to claim 2, characterized in that, The specific surface area of ​​the porous linden wood / mycelium composite carbon powder described in S2 is 400.82 m². 2 / g-487.33 m 2 / g.

8. The application of a self-assembled mycelial flexible carbon electrode material based on claim 1 in lithium-ion battery anode materials and battery packs.

9. The application according to claim 8, characterized in that, The self-assembled mycelial flexible carbon electrode material used in lithium-ion battery anode materials includes the following steps: mixing the self-assembled mycelial flexible carbon electrode material with conductive agent carbon black and binder PVDF to form a slurry, coating it onto a copper current collector, drying it, and then stamping it with a stamping machine to obtain the lithium-ion battery anode material.

10. The application according to claim 9, characterized in that, The mass ratio of the self-assembled mycelial flexible carbon electrode material to the conductive agent carbon black and the binder PVDF is 6-10:2:1.

Citation Information

Patent Citations

  • Lignin-based hard carbon / carbon nanotube composite material and preparation method and application thereof in negative electrode materials of lithium ion batteries

    CN107959006A

  • Method for preparing porous carbon materials from waste black liquor activated by bacteria and application of porous carbon materials

    CN109160505A

  • Method for preparing carbon electrode material by constructing wood pore structure based on fungal method

    CN112927954A

  • Preparation method of sodium ion battery hard carbon negative electrode material

    CN120398026A

  • Filamentous organism-derived carbon-based materials, and methods of making and using same

    WO2018075112A1

Cited By

  • Degradable flexible conductive mycelium material and preparation method thereof

    CN117625407A

  • Degradable flexible conductive mycelium material and preparation method thereof

    CN117625407B